Innovative Technologies in the Monitoring of the Age-Related Cataract - T. N. Kiseleva; M. S. Zaitsev (Oftalʹmologiâ, 2023)
Literature review is devoted to modern high-technology instrumental methods of the lens evaluation, which have been developed to improve efficiency of the diagnostics and management of cataract in ophthalmological clinical practice. The slit-lamp examination of lens and retroillumination images are used for subjective assessment of cataract according to LOCS III grading system. Currently objective methods of lens evaluation have practical value and provide information about early age-related changes of crystalline lens with the quantitative assessment of the severity of opacities including the optical and ultrasound examinations. Optical methods include densitometry using Scheimpflug images obtained from applications to quantify the localization of lens opacities and their progression rate. Another method is the intensity distribution analysis of the wave front of the optical aberrations according to grading cataract severity with the objective scatter index (OSI) obtained by double-pass technology. Moreover the optical quantitative assessment of lens opacities is carried out by the Shack—Hartmann wave front sensor to identify the grade of nuclear opalescence (N-type) with the Lens Opacities Classification System III. This method is very helpful in nuclear cataract. Swept source optical coherent tomography (SS-OCT) with variable length of wave and high frequency detector is used for the density measurements of nuclear and cortical opacities of lens imaging in micro- and macro dimensional scale. Ultrasound biomicroscopy is the most informative ultrasonic diagnostic method for the evaluation of acoustic density and early age-related changes of lens. Current high-informative methods of quantitative assessment of the optical density of lens are helpful in determination of indications for surgery, the optimization of phacoemulsification settings and prevention of intraoperative complications. The use of high-technologic methods demonstrated the effectiveness of eye drops 0,005 % pirenoxine in early lens opacities management.